Arterial stiffness acute changes following aerobic exercise in males with and without hypertension - Yiran Zang; Xiong Ding; Mao Xiang Zhao; Xiaoling Zhang; Li Zhang; Shouling Wu; Lixia Sun (The Journal of Clinical Hypertension, 2022)
Abstract While regular exercise exposure is considered the most effective therapy to reduce arterial stiffness, the effect of acute exercise training on arterial stiffness in adults with different blood pressure (BP) levels remains unclear. The authors aimed to investigate the effects of acute aerobic exercise on arterial stiffness in male with different BP levels. This cross‐sectional study utilized data for 1200 males aged 20–49 years from the Kailuan study cohort who participated in the fifth National Fitness Monitoring project. A total of 940 participants (621 in the non‐hypertensive group and 319 in the hypertensive group) aged 36.82 ± 7.76 who completed a twice‐quantitative cycle ergometer exercise and measure of brachial‐ankle pulse wave velocity (baPWV) at both the baseline and immediately after exercise were included in this study. The baPWV was decreased after acute aerobic exercise in the non‐hypertension and hypertension groups (Δ 40.29 [95% confidence interval [CI], −47.72 to −32.86] vs. Δ20.45 [95% CI, −31.32 to −9.58] cm/s). Participants without hypertension showed a greater decrease in baPWV (Δ 19.84 [95% CI, −33.83 to −5.84] cm/s) than participants with hypertension. Aerobic exercise had an acute positive effect on arterial stiffness. This study provides evidence of a greater reduction in arterial stiffness in individuals without hypertension than in those with hypertension.